702 The Role of Scapular Morphology in Traumatic Rotator Cuff Tears and Greater Tuberosity Fractures: A Retrospective Study. (12th October 2021) - de Stadler, K; Musbahi, O; Ibrahim, E
Abstract: Aim: Traumatic Rotator Cuff Tears(RCT) and Greater Tuberosity fractures(GT) are associated with high morbidity and reduced quality of life. Diagnostic and treatment pathways for both RCT and GT fractures are different. In this study we look at whether scapular morphology features can aid in our understanding of these traumatic injuries and influence patient pathways. Method: A retrospective study was conducted at 2 hospitals. All patients between the period of 2010 and 2020 with Traumatic GT fractures or RCT were identified. Patients were case matched by age and laterality of injury. Primary outcome measurement was the Critical Shoulder Angle(CSA) and timing to further imaging. Statistical analysis was conducted using STATA™. Results: Eighty patients met the inclusion criteria(40 traumatic RCT and 40 GT). Mean age was 61.8 years with 58(72.5%) left sided injuries. The difference between RCT and GT was 3.96 degrees(95% CI 2.5 to 5.41, p < 0.05). An CSA of 33.73 gave a sensitivity of 0.68 and a specificity of 0.8 to differentiate between RCT and GT fractures. The Area under the Curve(AUC) was 0.8 indicating high reliability. The overall difference in presentation to further scan between the 2 groups was 78. 3 days( P < 0.05, 95% CI 48.7 – 108). Conclusions: Patients with a traumatic RCT and GT fractures have different scapular morphology and radiographic features which predisposes them to have these injuries. Patients presenting with a traumatic RCT are more likely to have a higher CSA and have a greater delay to further scan.